Überzeugungs- und Überredungsmittel in mündlichen Aufforderungsakten im deutsch-italienischen Sprachvergleich - Venuti, Ilaria; Hinterhölzl, Roland (Linguistik Online, 2019)
The purpose of this study is to draw a comparison between the realization of requestive speech acts in Italian and in German, and to investigate the different strategies of persuasion in the two speech communities, with a particular attention to the relationship between efficiency and politeness.The empirical part of the study consists in the comparison of 320 requests formulated by Italian and German speakers. Linguistic data were elicited by means of a discourse completion test containing four socio-pragmatic situations. Realizations of requests were analysed according to the Cross-Cultural Speech Act Realization Project’s (CCSARP) Coding Manual, reported in Blum-Kulka, House and Kasper (1989), and discussed at two levels: the cross cultural variation and the situational variation.Results show that both groups of participants are perfectly aware of the differences between the situations proposed and tailor their requests according to the context. It is found that both groups of subjects rely heavily on conventionally indirect strategies. On the whole, German speakers appear to use more indirect request strategies than their Italian counterparts, and at the same time choose with a higher frequency phrasal, lexical and syntactical modificators. Italian speakers tend to select slightly lower levels of indirectness but compensate with a consistently larger use of external modificators. Moreover, both Italian and German speakers seem to recur more often to strategies of Überzeugung, probably because the most used modificator for both groups of respondents is the Grounder.Our results differ in interesting ways from general expectations in the situation in which the face threat is arguably the highest, calling for further investigation of the difference in the perception of the social parameters determining the rated face threat between the two speech communities. Deeper insights into the link between indirectness and politeness in the two cultures at issue are also needed in order to understand the reasons behind the pragmatic choices observed.